In vitro mechanism of action on insulin release of S-22068, a new putative antidiabetic compound. - Le Brigand, L; Virsolvy, A; Manechez, D; Godfroid, J; Guardiola-Lemaître, B; Gribble, F; Ashcroft, F; Bataille, D (1999)
1. The MIN6 cell line derived from in vivo immortalized insulin-secreting pancreatic beta cells was used to study the insulin-releasing capacity and the cellular mode of action of S-22068, a newly synthesized imidazoline compound known for its antidiabetic effect in vivo. 2. S-22068, was able to release insulin from MIN6 cells in a dose-dependent manner with a half-maximal stimulation at 100 micronM. Its efficacy (8 fold over the basal value), which did not differ whatever the glucose concentration (stimulatory or not), was intermediate between that of sulphonylurea and that of efaroxan. 3. Similarly to sulphonylureas and classical imidazolines, S-22068 blocked K(ATP) channels and, in turn, opened nifedipine-sensitive voltage-dependent Ca2+ channels, triggering Ca2+ entry. 4. Similarly to other imidazolines, S-22068 induced a closure of cloned K(ATP) channels injected to Xenopus oocytes by interacting with the pore-forming Kir6.2 moiety. 5. S-22068 did not interact with the sulphonylurea binding site nor with the non-I1 and non-I2 imidazoline site evidenced in the beta cells that is recognized by the imidazoline compounds efaroxan, phentolamine and RX821002. 6. We conclude that S-22068 is a novel imidazoline compound which stimulates insulin release via interaction with an original site present on the Kir6.2 moiety of the beta cell K(ATP) channels.